Application of Ozone and Oxygen to Reduce Chemical Oxygen Demand and Hydrogen Sulfide from a Recovered Paper Processing Plant - Patricia A. Terry (International Journal of Chemical Engineering)
A pilot study was performed at the Fox River Fiber recovered paper processing company in DePere, Wisconsin, to determine the extent to which injection of oxygen and ozone could reduce the high chemical oxygen demand, COD, in the effluent and the effectiveness of the ozone/oxygen stream in suppressing production of hydrogen sulfide gas in downstream sewage lines. Adaptive Ozone Solutions, LLC, supplied the oxygen/ozone generation and injection system. Samples were analyzed both before and after oxygen/ozone injection. Hydrogen sulfide gas was continuously monitored at sewer stations downstream of Fox River Fiber. Results showed that with a very short contact time, effluent COD was reduced by over 15%. A simple kinetic model predicts that a contact time of fewer than 30 minutes could reduce COD by as much as 60%. In addition, downstream hydrogen sulfide gas production in the sewage mains was also better controlled, such that costly Bioxide applications could be reduced.